Gluten restriction in irritable bowel syndrome, yes or no?: a GRADE-assessed systematic review and meta-analysis - Arabpour, Erfan; Alijanzadeh, Dorsa; Sadeghi, Amir; Khoshdel, Sina; Hekmatdoost, Azita; Kord-Varkaneh, Hamed; Abdehagh, Mohammad (Frontiers in Nutrition, 2023)
Background: More than half of patients with irritable bowel syndrome (IBS) report aggravating their symptoms with certain foods. Currently, Low fermentable oligo-, di- and monosaccharides and polyols diet (LFD) is the most accepted dietary intervention for IBS. Recent randomized controlled trials (RCTs) have been suggested that gluten restriction may reduce the symptoms of patients with IBS. However, the results from these studies are conflicting. This study filled this knowledge gap by evaluating the impact of the gluten-free diet (GFD) on IBS symptoms. Methods: A systematic search was carried out in Pubmed/Medline, Cochrane CENTRAL, Scopus, and Web of Science up to April 2023. A random-effect model was applied to estimate the standardized mean difference (SMD) and 95% confidence interval (95% CI) for each outcome. Results: A total of 9 controlled trials were included in the meta-analysis. In contrast to gluten-containing diet, GFD was unable to reduce overall symptoms (SMD − 0.31; 95% CI −0.92, 0.31), bloating (SMD -0.37; 95% CI -1.03, 0.30) and quality of life (SMD -0.12, 95% CI -0.64, 0.39); but had a slight trend to reduce abdominal pain (SMD – 0.68; 95% CI −1.36, -0.00). Also, LFD significantly reduced the IBS-Severity score system (SMD 0.66, 95% CI 0.31, 1.01) and improved quality of life (SMD -0.36, 95% CI -0.70, -0.01), compared to GFD. Conclusions: A GFD is not robust enough to be routinely recommended for IBS patients, and its efficacy is significantly lower than that of an LFD. Only a certain subgroup of IBS patients may benefit from GFD; further studies are needed to target this subgroup.